EFEKTIVITAS DAN DAMPAK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT-MANDIRI PERDESAAN (PNPM-MPd) DI KECAMATAN DENPASAR UTARA - Kirwati, Nyoman; Setiawina, N. Djinar; Yasa, I.G.W Murjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.02.TAHUN 2018DO - 10.24843/EEB.2018.v07.i02.p03, 2018)
The purpose of the study was to analyze the effectiveness of the National Program for Community Empowerment-Mandiri Rural in District of North Denpasar, to analyze the differences in income, employment opportunities for poor households before and after attending the National Community Empowerment Program-Mandiri Rural in District of North Denpasar and to identify the weaknesses of the National Program for Community Empowerment in Rural Self- District of North Denpasar. Results of hypothesis testing carried out showed that the effectiveness of the implementation of the National Program for Community Empowerment - Mandiri in Rural Areas (PNPM-MP) in District of North Denpasar as very effective in terms of four indicators namely: the program objectives, program objectives, funding programs, and allocation of funds program. Judging from the impact of PNPM Mandiri to improve household incomes in District of North Denpasar conducted showed that the implementation of the Program PNPM Rural in North Denpasar District had enough impact on increasing incomes of the poor and increase employment opportunities for the poor. Job opportunities after the poor households get help National Community Empowerment Program-Independent Rural (PNPM-MP) in the District of North Denpasar positive effect increasing employment opportunities of poor households.